2020
DOI: 10.1038/s41419-020-02891-2
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules targeting RORγt inhibit autoimmune disease by suppressing Th17 cell differentiation

Abstract: Th17 cells, a lymphocyte subpopulation that is characterized by the expression of the transcription factor "retinoic acid receptor-related orphan receptor gamma-t" (RORγt), plays an important role in the pathogenesis of autoimmune disease. The current study was set up to discover novel and non-steroidal small-molecule inverse agonists of RORγt and to determine their effects on autoimmune disease. Structure-based virtual screening (SBVS) was used to find compounds targeting RORγt. Flow cytometry was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Several RORγt antagonists are used in ongoing clinical trials, such as GSK805 and TAK-828F, which both have shown prospective efficacy in preclinical models and animal models of inflammatory diseases ( 125 , 126 ). However, several questions remain about RORγt antagonism, including potential mechanisms of action, key target cells and effects on the homeostatic balance within Th17 cells and Treg cells ( 127 ). Furthermore, miR-155 is closely related to the differentiation of CD4 + T cells to Th17 cells.…”
Section: Therapeutic Implications Of Apmentioning
confidence: 99%
“…Several RORγt antagonists are used in ongoing clinical trials, such as GSK805 and TAK-828F, which both have shown prospective efficacy in preclinical models and animal models of inflammatory diseases ( 125 , 126 ). However, several questions remain about RORγt antagonism, including potential mechanisms of action, key target cells and effects on the homeostatic balance within Th17 cells and Treg cells ( 127 ). Furthermore, miR-155 is closely related to the differentiation of CD4 + T cells to Th17 cells.…”
Section: Therapeutic Implications Of Apmentioning
confidence: 99%
“…IL-17A is a powerful proinflammatory factor that can be vastly secreted by Th17 cells; moreover, IL-17A also can act on a variety of cell types for the inducing expression of cytokines including proinflammatory cytokines, chemokines, and matrix metalloproteinases [ 11 , 12 ]. Similar to Th1 and Th2 cell subgroups, the steroid receptor type nuclear receptor ROR γ t also is the corresponding major regulators of Th17 cells [ 13 ]. Studies have shown that ROR γ t can promote the expression of IL-17A and IL-17F by naive T cells and therefore regulate the secretion of IL-17 [ 14 ], while regulatory T (Treg) cells which can inhibit immune response play an important role in immune balance maintaining and regulating immunity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are surprising considering previous studies of RORC inhibition in a variety of inflammatory models including antigen-induced arthritis ( 17 ), imiquimod-induced psoriasis ( 21 ), IL-23 induced skin inflammation ( 30 ), intestinal inflammation ( 22 , 31 ). Recently, Tan et al ( 24 ) showed the reduced clinical severity of experimental autoimmune uveitis (EAU), and EAE using two different RORc antagonists (CQMU151 and CQMU152) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic lack of RORγt protected mice against experimental autoimmune encephalomyelitis (EAE), induced defects in Th17 differentiation and prevented T-cell-transfer-mediated colitis ( 8 , 20 ). Pre-clinical studies in animal models, including imiquimod-induced psoriasis ( 21 ), spontaneous colonic inflammation ( 22 ), antigen induced arthritis ( 17 ), EAE ( 23 ), and experimental autoimmune uveitis (EAU) ( 24 ), confirmed that RORC inhibition markedly reduces local and systemic IL-17A levels and decreases tissue inflammation. Moreover, expression of IL-17F and IL-22 was also reduced upon in vivo RORC inhibition ( 21 , 23 ).…”
Section: Introductionmentioning
confidence: 95%